Upaya Kepala Madrasah Dalam Meningkatkan Kompetensi Profesional Guru - Akhyar, Nurul (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Teacher competency enhancement must be carried out by the head of the madrasah continuously so that teacher competency always increases and the teacher becomes a great and qualified teacher. The objectives of this study include; 1) Describe the headmaster's efforts in improving the competence of Madrasah Ibtidaiyah Al-Maarif 02 Singosari teachers. 2) Description of the supporting and inhibiting factors that affect the head of the madrasah in enhancing the competence of teachers of the Madrasah Ibtidaiyah Al-Maarif 02 Singosari. To achieve the above objectives, the researcher used a qualitative approach with a type of descriptive research. The location of this study was conducted at MI Al-Maarif 02 Singosari Malang. The informants in this study were the head of the madrasa and the class teacher. The technique of collecting data uses interviews and documentation. To analyze the author's data using qualitative descriptive analysis. The findings of this study are: 1) the head of the madrasa conducts an effort that is formally done namely by Rutinan Meetings, includes training, teacher training and seminars, inter-teacher / KKG group studies, supervision and class visits and Conducting Assessments, while non-formal activities are by familiarizing discipline and always providing motivation with the aim of increasing the teacher's insight, providing opportunities for teachers to improve the spirit of discipline and teacher skills,2) Supporting factors affecting the madrasah head in increasing teacher competency are the fulfillment of madrasah infrastructure that is fulfilled, enthusiastic and enthusiastic about the teachers participating in the training, and the support of the foundation while the inhibiting factors faced by the madrasa principals are; the head of the madrasa itself and the teacher who is not in the madrasa.